Get to know the Tafsir of the Nusantara in the 20th Century: Tafsir Al-Azhar by Buya Hamka - Arrahman Aji Prabowo; Wan Alif Ihza Mahendra; Ahmad Roihan; Daffa Haikal; Muhammad Alfi Khairi; Khairul Aula Siregar; Cikal Awandano; Mega Puspita; Nurfadhillah Winata Zendrato; Opi Salamah; Salahuddin Harahap (Values: Jurnal Kajian Islam Multidisiplin, 2025)
Buya Hamka's Tafsir Al-Azhar is one of the important intellectual legacies in the study of Indonesian tafsir in the 20th century. This interpretation was compiled by the Indonesian cleric and scholar, Buya Hamka, who is not only known as a mufassir, but also a writer, thinker and public figure. Tafsir Al-Azhar offers a classical Islamic scientific approach, modern thought, and the socio-cultural context of Indonesian society. Hamka uses a simple language style, logical arguments, and emphasizes universal Islamic values, such as justice, humanity, and moderation. This interpretation also reflects the spirit of Islamic reform, an effort to respond to the challenges of the times, and voices the relevance of the Al-Qur'an in everyday life. In the study of Indonesian tafsir, Tafsir Al-Azhar is an important reference that represents thematic and contextual styles of interpretation, making it relevant for modern readers today.